TEACHING READING THROUGH KNOW-WANT-LEARNED (KWL) STRATEGY: The effects and benefits - Bustami Usman; Ika Apriani Fata; Ratih Pratiwi (Englisia: Journal of Language, Education, and Humanities, 2018)
This study aimed to chart out the effects of teaching reading using Know-Want-Learned (KWL) strategy of Blachowicz and Ogle. This study employed quantitative method by having one pre-test and posttest research design, conducted at SMPN 2 Kejuruan Muda, Aceh Tamiang District, with a total sample of 26 students. The test was analyzed by using t-test.  The study revealed that there was an improvement from the pre-test to the posttest and that the teacher had implemented KWL strategy accordingly so that the students improved their reading comprehension skill. In addition, KWL is one of the basic strategies developed to know the extent of learners’ ability and the way they commit it on their own. Thus, the strategy itself has an effect to trigger the students to be autonomous learners. However, it is suggested that the teachers modify some steps in the KWL procedures to eventually motivate the students in learning reading.